2020
DOI: 10.1136/bmjopen-2020-038963
|View full text |Cite
|
Sign up to set email alerts
|

Does electronic consent improve the logistics and uptake of HPV vaccination in adolescent girls? A mixed-methods theory informed evaluation of a pilot intervention

Abstract: ObjectivesTo evaluate the usability and acceptability of an electronic consent pilot intervention for school-based immunisations and assess its impact on consent form returns and human papilloma virus (HPV) vaccine uptake.DesignMixed-methods theory-informed study applying qualitative methods to examine the usability and acceptability of the intervention and quantitative methods to assess its impact.Setting and participantsThe intervention was piloted in 14 secondary schools in seven London boroughs in 2018. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Two original items highlighted that there must be sufficient provisions for soliciting the assent of children [ 19 , 52 ]. In other words, for research involving children, ample time and resources should be given to both the children and their parents to understand and reach joint consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Two original items highlighted that there must be sufficient provisions for soliciting the assent of children [ 19 , 52 ]. In other words, for research involving children, ample time and resources should be given to both the children and their parents to understand and reach joint consensus.…”
Section: Discussionmentioning
confidence: 99%
“…While the traditional paper consent school delivery model is widely accepted (Paul & Fabio, 2014) However, it is worth noting that the move from paper consent to eConsent was not straightforward, while the potential benefits were widely understood, it is often difficult to adapt to new ways of working which remove some level of control from schools (Chantler et al, 2020). The new process means that schools no longer required to distribute paper consent forms, and the Immunization Team no longer rely on pupils giving form to parents and returning them completed on the day of immunization.…”
Section: Discussionmentioning
confidence: 99%
“…However, Yahia et al found that when conducting novel, multi-faceted, and interdisciplinary HPV campaigns, it is possible to increase HPV knowledge and vaccination rates [ 8 ]. Improving accurate knowledge about HPV, resulting cancers and outcomes, and increasing vaccination uptake requires a collaborative and coordinated effort among many including parents and family members [ 4 , 14 16 ], healthcare professionals [ 17 ], adolescent boys and girls [ 15 , 18 ], and those within the recommended age guidelines for the HPV vaccine [ 5 , 19 ]. To expand the literature and encompass more adults within a range of the HPV vaccine age, we designed an HPV study to survey students, staff, and faculty at a public, state university at three-year increments between 2016 and 2022.…”
Section: Introductionmentioning
confidence: 99%